Saddle up for murder - Hearon, Leigh (Hearon, Leigh. Carson Stables mystery., 2016)
At first, horse trainer and Carson Stables owner Annie Carson blames the random losses of local livestock on feral animals stalking Olympic Peninsula county's farms and ranches. But when one of her own flock is found savagely slaughtered, it gets personal. Then it turns dangerous, when Annie discovers the body of a young woman hanging in her new hay barn. Suddenly, she's up to her neck in complicated mysteries--one involving her private life. But her sleuthing skills aren't exactly welcome by the sheriff. And as she uncovers a clue to the killer's identity, Annie fears she's leading a deadly trail straight to her door.